Physiological Roles of Short-Chain and Long-Chain Menaquinones (Vitamin K2) in Lactococcus cremoris - Liu, Yue; Charamis, Nikolaos; Boeren, Sjef; Blok, Joost; Lewis, Alisha Geraldine; Smid, Eddy J.; Abee, Tjakko (Frontiers in Microbiology, 2022)
Lactococcus cremoris and L. lactis are well-known for their occurrence and applications in dairy fermentations, but their niche extends to a range of natural and food production environments. L. cremoris and L. lactis produce MKs (vitamin K2), mainly as the long-chain forms represented by MK-9 and MK-8, and a detectable amount of short-chain forms represented by MK-3. The physiological significance of the different MK forms in the lifestyle of these bacterial species has not been investigated extensively. In this study, we used L. cremoris MG1363 to construct mutants producing different MK profiles by deletion of genes encoding (i) a menaquinone-specific isochorismate synthase, (ii) a geranyltranstransferase and (iii) a prenyl diphosphate synthase. These gene deletions resulted in (i) a non-MK producer (ΔmenF), (ii) a presumed MK-1 producer (ΔispA) and (iii) a MK-3 producer (Δllmg_0196), respectively. By examining the phenotypes of the MG1363 wildtype strain and respective mutants, including biomass accumulation, stationary phase survival, oxygen consumption, primary metabolites, azo dye/copper reduction, and proteomes, under aerobic, anaerobic and respiration-permissive conditions, we could infer that short-chain MKs like MK-1 and MK-3 are preferred to mediate extracellular electron transfer and reaction with extracellular oxygen, while the long-chain MKs like MK-9 and MK-8 are more efficient in aerobic respiratory electron transport chain. The different electron transfer routes mediated by short-chain and long-chain MKs likely support growth and survival of L. cremoris in a range of (transiently) anaerobic and aerobic niches including food fermentations, highlighting the physiological significance of diverse MKs in L. cremoris.